2016
DOI: 10.1155/2016/5798593
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Polycyclic Aromatic Hydrocarbon-Degrading Bacterial Isolates to Contribute to Soil Fertility

Abstract: Restoration of polycyclic aromatic hydrocarbon- (PAH-) polluted sites is presently a major challenge in agroforestry. Consequently, microorganisms with PAH-degradation ability and soil fertility improvement attributes are sought after in order to achieve sustainable remediation of polluted sites. This study isolated PAH-degrading bacteria from enriched cultures of spent automobile engine-oil polluted soil. Isolates' partial 16S rRNA genes were sequenced and taxonomically classified. Isolates were further scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Compost bioremediation of crude oil sludge had many role players, it enthused the growth and activities of indigenous fungi and bacteria for the subsequent degradation of PAH‐contaminated waste. A number of studies confirm the metabolism of petroleum hydrocarbons by fungi and bacteria that were isolated in the course of this study . The presence of fungi and bacteria in the compost depicts their co‐existence in a PAH‐contaminated environment and possibly co‐metabolism.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Compost bioremediation of crude oil sludge had many role players, it enthused the growth and activities of indigenous fungi and bacteria for the subsequent degradation of PAH‐contaminated waste. A number of studies confirm the metabolism of petroleum hydrocarbons by fungi and bacteria that were isolated in the course of this study . The presence of fungi and bacteria in the compost depicts their co‐existence in a PAH‐contaminated environment and possibly co‐metabolism.…”
Section: Discussionsupporting
confidence: 71%
“…A number of studies confirm the metabolism of petroleum hydrocarbons by fungi and bacteria that were isolated in the course of this study. [49][50][51][52] The presence of fungi and bacteria in the compost depicts their co-existence in a PAHcontaminated environment and possibly co-metabolism. A combination of fungi and bacteria synergistically enhanced the rate of degradation of HMW PAHs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Acinetobacter , Stenotrophomonas and Sanguibacter were found to dominate the meconium ecosystem. These aerobic microorganisms are common inhabitants of soil or aquatic ecosystems, but occasionally they have been isolated as opportunistic bacteria from animal hosts . On the other side, meconium also contained Aerococcus at relevant percentages (relative abundance 9%).…”
Section: Discussionmentioning
confidence: 99%
“…Soil microorganisms play vital roles in the maintenance of soil function [15] and significantly influence agricultural soil productivity, plant growth, and crop quality [16][17][18]. Numerous studies have suggested that microbial diversity can serve as an indicator of disease susceptibility in medicinal plants, and microbial communities have important roles in the maintenance of plant health and soil fertility [19][20][21].…”
Section: Introductionmentioning
confidence: 99%